Influence of In and Sn compositions on the reactivity of Al–Ga–In–Sn alloys with water. (2nd March 2017) - He, T.T.; Wang, W.; Chen, W.; Chen, D.M.; Yang, K.
Abstract: Al alloys containing 3 wt.% of Ga, In and Sn were prepared using arc melting technique. Their microstructures were investigated by means of X-ray diffraction and scanning electron microscope with energy dispersed X-ray, and interface reactions were detected using differential scanning calorimeter. The alloys consist of different low melting point phases at Al grain boundaries, which melting points depend on the compositions of alloys. Al-water reactivities were investigated under different water temperatures. The reaction temperatures above 40 °C are much higher than the melting point of ternary Ga–In–Sn (GIS) eutectic of 10.4 °C, indicating that GIS eutectic is already not the mechanism of Al-water reaction. The reaction temperature and the reaction rate of alloys vary with the mass ratio of In/Sn. Reasons concerning the microstructure changes and Al-water reactivities are discussed. Highlights: The In/Sn mass ratios of β and γ depend on alloy compositions. The melting point of grain boundary phases determines the reaction temperature of Al-water. β phase dominates Al-water reaction of Al–Ga–In–Sn alloy. The reaction temperature and reaction rate of Al-water can be adjusted by changing alloy compositions.